ARTS AND CULTURE EXHIBITION: CHARACTERISTICS OF MALUKU AS A MULTICULTURAL COMMUNITY IN MULTICULTURAL EDUCATION COURSES - jenny koce matitaputty (Universitas Sultan Ageng Tirtayasa, 2019)
In the context of multiculturalism, education must reward the reality of plurality. Multicultural education is truly felt to have a very important space to be presented in the world of education as a solution to the appreciation of the plurality of Indonesian society. Performing arts and culture is one of the concrete steps to teach students as prospective teachers to be able to recognize the various characteristics of Maluku society as a multicultural society. This study used a qualitative method and was conducted on students of the historical education study program at the Faculty of Education and Teacher Training at Pattimura University. Data collection using observation techniques, interviews and questionnaires. The results of the study show that through art and cultural performance activities that are packaged in multicultural education learning clarify the characteristics of Maluku as a multicultural society, increase students' knowledge to appreciate the plurality of Maluku as a multicultural society, increase student awareness to be part of the people of Maluku, Indonesia and the World in maintaining world peace as well as providing hope to students in building the spirit of life of orang Basudara in Maluku.